Impact of Regional Revenue and Expenditure Budgets and Economic Growth on the Human Development Index - Mappaujung Maknun (Advances in Economics & Financial Studies, 2023)
This study aims to examine and analyze the Influence of Expenditure Budget and Economic Growth on the Human Development Index in Makassar City. The data sources for this research were taken from the Regional Financial and Asset Management Agency (BPKAD) and the Central Bureau of Statistics (BPS) for Makassar City. The data collection technique uses documentation in the form of Budget Realization Reports and Gross Domestic Product based on Current Prices according to Expenditures from 2010-2019. The data that has been collected will be analyzed with several stages of testing, including descriptive statistical tests, classic assumption tests consisting of (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), and testing of all hypotheses which will be proven through a coefficient of determination test, test partial (t test) and simultaneous test (f test). The results of the research that has been done state that the APBD variable has a very weak effect because it has no real effect and is not significant to the Human Development Index in Makassar City. While the variable Economic Growth has a positive and significant effect on the Human Development Index, which means that if Economic Growth is increased it will increase the value of the Human Development index in Makassar City